Faktor-Faktor yang Mempengaruhi Penyalahgunaan Narkotika di Kalangan Mahasiswa di Bandar Lampung - Zainudin Hasan; I Made Agus Deny Kusuma (Pusat Riset dan Inovasi Nasional, 2025)
The drug problem in Bandar Lampung, especially among teenagers, is still a pressing problem. This is proven by the increasing number of drug addicts or abusers, even among young people. Along with the disclosure of drug cases that are increasingly diverse in pattern and increasingly massive syndicate networks, there are individuals who abuse their positions to become drug dealers. Currently, the people of Lampung are facing a very worrying situation due to the large number of illegal drug trafficking. This concern is increasing as a result of the illegal distribution of drugs that have spread throughout society, including the younger generation. This will have a major impact on the future of the country. The behavior of some teenagers who ignore applicable norms and laws, as well as the environment of friendship or association, are some of the factors that cause increased drug use among teenagers. This study uses a legal problem approach because many teenagers continue to abuse drugs in their daily lives. This primary data comes from the field and comes from interviews with the drug eradication p2m of the Lampung Province BNNP. Based on the author's research and discussion, it can be concluded that the function of the BNN in combating narcotics crimes class 1 is to prevent and eliminate drug abuse and illicit trafficking (P4GN). The BNN is also responsible for investigating, prosecuting, and examining cases of class 1 narcotics abuse by teenagers in Lampung province.